Pemisahan Harta Bersama Tanpa Adanya Perjanjian Perkawinan pada Perkawinan Campuran (Mixed Marriage) - Puteri, Erriyanti Samuhedah; Yustikarini, Meliyana (Universitas Batanghari Jambi, 2024)
This study has the aim of knowing the legal consequences that arise against property in mixed marriage and knowing the legal arrangements for the separation of joint property in mixed marriage without a marriage agreement. Joint property is one of the legal consequences that arise in marriage. In a marriage without a marriage agreement, joint property will be created. However, conflicts will arise if what happens is a mixed marriage. This writing has the aim of knowing how the legal arrangements for the separation of joint property in a mixed marriage without a marriage agreement and what legal consequences arise for property in a mixed marriage. In this research the author uses doctrinal legal research methods. The conclusion that can be drawn in this study is that the legal consequences arising from property in a mixed marriage if referred to based on Law No. 1 of 1974 concerning Marriage, if the parties do not make a marriage agreement, there will be joint property.